KONSUMSI BAHAN BAKAR PADA MOBIL KIJANG KF40 MENGGUNAKAN PENGAPIAN KONVENSIONAL PLATINA DENGAN SISTEM PENGAPIAN CDI (CAPASITOR DISCHARGE IGNITION) - i puji setiawan, Deni; Anam, Khoirul (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2021)
In the development of the ignition system, the conventional ignition system will be marginalized and may not be used anymore because it is considered ineffective. What was originally using a conventional platinum ignition system on the Kijang kf40 car can be replaced or modified with a CDI electronic ignition system, in which here there are slight changes and additional components. This electronic ignition system for conventional vehicles is called the "CDI / Capacitor Discharge Ignition ignition system".Pertamax applies ecosave technology, which is a technology that is able to clean the inside of the engine, with an octane rating of 92. That way, the engine combustion will be more perfect. This test uses rpm 800, 1000, 1200. This study aims to determine the effect of using platinum ignition and cdi ignition with Pertamax fuel.Based on the results of Pertamax fuel testing for platinum ignition and CDI, the percentage of the largest value in CDI ignition / Capacitor Discharge Ignition 0.7 Milliliter is more efficient compared to platinum ignition at 800 rpm engine speed. While at 1000 RPM, CDI ignition / Discharge Ignition capacitors are 1.2 milliliter more efficient than platinum ignition. At 1,200 RPM, CDI ignition / Capacitor Discharge Ignition is 3.1 milliliter more efficient than Platinum ignition. From several rpms tested, it shows that the higher the RPM, the greater the difference in fuel consumption. Between the two tested ignitions.Keywords: ignition system, conventional platinum, CDI ignition / Capacitor Discharg